2017
DOI: 10.1186/s13287-017-0618-y
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-3 enhances the migration of human mesenchymal stem cells by regulating expression of CXCR4

Abstract: BackgroundMesenchymal stem cells (MSCs) represent an important source for cell therapy in regenerative medicine. MSCs have shown promising results for repair of damaged tissues in various degenerative diseases in animal models and also in human clinical trials. However, little is known about the factors that could enhance the migration and tissue-specific engraftment of exogenously infused MSCs for successful regenerative cell therapy. Previously, we have reported that interleukin-3 (IL-3) prevents bone and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 60 publications
(71 reference statements)
0
37
0
Order By: Relevance
“…On the background of their previous report that, IL-3 prevents bone and cartilage damage, and increases the differentiation potential of MSCs into functional osteoblasts, Barhanpurkar-Naik et al [83] further investigate the role of IL-3 in the migration of MSCs. They report that MSCs conditioned with IL-3, overexpress CXCR4 which causes increased migration towards SDF-1α (i.e.…”
Section: Improving Migrationmentioning
confidence: 99%
“…On the background of their previous report that, IL-3 prevents bone and cartilage damage, and increases the differentiation potential of MSCs into functional osteoblasts, Barhanpurkar-Naik et al [83] further investigate the role of IL-3 in the migration of MSCs. They report that MSCs conditioned with IL-3, overexpress CXCR4 which causes increased migration towards SDF-1α (i.e.…”
Section: Improving Migrationmentioning
confidence: 99%
“…Different molecules are involved in or necessary for the different steps in the homing process, and chemokines receptors (G‐protein coupled receptors) represent the main group . It has been extensively demonstrated that the CXCR4–stromal‐derived factor‐1 (CXCL12/SDF‐1) axis is critical for bone marrow homing, and a number of the other cytokines and growth factors such as CCL2/MCP1, TNFα, CXCL10/IP10 have been shown to increase migration in vitro …”
mentioning
confidence: 99%
“…It is well known that exposure of mesenchymal stem cells with IL-3 could increase cell migration and wound closure. On the other hand, Barhanpurkar-Naik showed that IL-3 stimulates cell migration in the mesenchymal stem and also fastens wound closure [33]. In this context, the level of the IL-3 was higher in the REO-NLCs-treated animals.…”
Section: Discussionmentioning
confidence: 89%
“…REO-NLCs increased SDF-1a in comparison to the control group. It is accepted that SDF-1a is significantly increased in the injured tissues and facilitates the migration and engraftment of circulation of CXCR4-positive cells [33]. With regards to increasing the level of IL-3 and SDF-1a in REO-NLCs-treated animals, it can be claimed that therapeutic gels helped to trigger the wound healing.…”
Section: Discussionmentioning
confidence: 99%